2010
DOI: 10.7899/1042-5055-24.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Chiropractic Students and Research: Assessing the Research Culture at a North American Chiropractic College

Abstract: of Chiropractic FloridaPurpose: To continue positive professional growth and boost research endeavors, chiropractic institutions need to develop a research-oriented foundation and produce a larger body of researchers. The purpose of this study was to provide a current analysis of the research culture among students at Palmer College of Chiropractic Florida. This study will gain insight toward the research contributions of the next generation of chiropractors and identify the difficulties toward participation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Numerous studies investigating students' attitudes towards research have been published in the medical, nursing, physical therapy, occupational therapy, chiropractic and other allied health occupational literature. [24][25][26][27][28][29][30][31][32] Although pharmacy students' attitudes towards postgraduate research have been investigated in the past, these early studies were conducted at a time when postgraduate education mainly involved laboratory-based research in pharmaceutics, pharmacology or medicinal chemistry. [33][34][35][36] To date, no published study has investigated the attitudes of pharmacy students towards PPR at each stage of the undergraduate programme.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies investigating students' attitudes towards research have been published in the medical, nursing, physical therapy, occupational therapy, chiropractic and other allied health occupational literature. [24][25][26][27][28][29][30][31][32] Although pharmacy students' attitudes towards postgraduate research have been investigated in the past, these early studies were conducted at a time when postgraduate education mainly involved laboratory-based research in pharmaceutics, pharmacology or medicinal chemistry. [33][34][35][36] To date, no published study has investigated the attitudes of pharmacy students towards PPR at each stage of the undergraduate programme.…”
Section: Introductionmentioning
confidence: 99%
“…Only 51% felt that they had the skills to conduct good research, a self-determined assessment that the authors felt was possibly inflated and perhaps could be explained by a ''disconnect in their understanding of research skills and quality research''. 17 Extracurricular activities and current employment were associated with higher ratings in all 4 domains across the student sample. This is a correlation, not a cause-and-effect relationship, and it would be conjecture to assume whether having these extra interests improves the outcome or whether the type of student who would have extra interests would also perhaps score better in the outcome domains.…”
Section: Discussionmentioning
confidence: 87%
“…[11][12][13][14][15][16][17][18][19] Studies on chiropractic students' attitudes specifically have also been done. For example, Newell and Cunliffe 19 conducted such a study on undergraduate students at McTimoney Chiropractic College and found that 64% of their 119 student respondents found research interesting, 54% thought it was difficult, and 75% considered chiropractic research to be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Few of the students believed that scientific research exploring the cost versus benefits ratio of physiotherapy treatment is necessary for positive growth in the physiotherapy profession. Weber 20 reported that students who replied ninety nine percent established that research was essential for positive development. 58% intended to involve in research programs proceeding to graduation, a group of participants had research experience.…”
Section: Discussionmentioning
confidence: 99%